1994
DOI: 10.1093/bja/73.6.767
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative or postoperative diclofenac for laparoscopic tuballigation

Abstract: We have compared the analgesic effects of diclofenac given before operation or immediately after operation in a randomized, double-blind, double-dummy study of 40 healthy female patients undergoing laparoscopic tubal ligation. Group 1 patients received diclofenac 75 mg as a 3-ml i.m. injection 1-2 h before operation and normal saline 3 ml i.m. immediately after surgery. Group 2 patients received normal saline 3 ml i.m. before operation and diclofenac 75 mg i.m. immediately after surgery. Outcome measures were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…A recent report by Rømsing et al 7 also demonstrated that, for tonsillectomy, preoperative intravenous ketorolac reduced the postoperative use of fentanyl more than postoperative administration. In contrast, Buggy et al 8 showed that administration of diclofenac i m prior to laparoscopic tubal ligation produced no additional benefit compared with postoperation administration. In our study, preoperative administration of flurbiprofen reduced postoperative pain more than postoperative administration during the 72 hr period monitored, not only at rest, but also on coughing.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…A recent report by Rømsing et al 7 also demonstrated that, for tonsillectomy, preoperative intravenous ketorolac reduced the postoperative use of fentanyl more than postoperative administration. In contrast, Buggy et al 8 showed that administration of diclofenac i m prior to laparoscopic tubal ligation produced no additional benefit compared with postoperation administration. In our study, preoperative administration of flurbiprofen reduced postoperative pain more than postoperative administration during the 72 hr period monitored, not only at rest, but also on coughing.…”
Section: Resultsmentioning
confidence: 95%
“…5 The preemptive efficacy of NSAIDs is controversial: not all studies have reported benefit. [5][6][7][8] We investigated whether flurbiprofen iv, given in a preemptive manner, reduce postoperative pain after abdominal hysterectomy .…”
mentioning
confidence: 99%
“…The meta-analysis showed that VAS scores in eight of the nine study arms reported a significant benefit for NSAIDs versus placebo and also reported that three study arms all reported a significant benefit for systemic NSAIDs versus placebo according the first analgesic request and use of supplementary analgesics. Conversely there are other recent studies showed that some NSAIDs have no preemptive effect in different surgical procedures (16)(17)(18).…”
Section: Discussionmentioning
confidence: 96%
“…Woolf et al (24) showed no difference with preoperative diclofenac from postoperative diclofenac in patients undergoing laparascopic tubal ligation. However, Buggy et al (25) and Gillberg et al (26) demonstrate that preoperative administration of ketorolac, piroxicam and diclofenac did reduce postoperative pain in patients undergoing laparoscopy. Our fi ndings support these results as well.…”
Section: Discussionmentioning
confidence: 98%